A Convergence of Traditions: Saint Lawrence Chapel, by Avanto Architects - Antonio Millán-Gómez (VLC Arquitectura)
Debates on the actuality of modern architecture by new contributions could be considered by critics as a deviation from its essence. In such a context, some works by Finnish studies exhibited at the Museum of Finnish Architecture in Spring, 2015 provide fresh approaches with their proposals and interest us here to reconsider architectural modernity with alterative readings. Project ideas are fused and converge towards new proposals in a process of continuity, from which only the concrete buildings experience, with enlightening phenomenal qualities, redeem us. We concentrate on a chapel by Avanto Architects in which interests from the second generation of modern architecture and the masters of Nordic Architecture can be appreciated.